Transition from Collegiate Track & Field: an Examination of Values and Commitment - (:unkn) unknown (My University, 2021)
This study provides a glimpse into psychological factors some of the 100,000 student-athletes who leave collegiate sport each year may face and adds to current understandings of ways to best serve collegiate student-athletes prior to their departure from collegiate sport. Drawing from the theories of Acceptance and Commitment Therapy and The Minnesota Theory of Work Adjustment, the study utilizes a population of former NCAA Division 1, 2, 3 and NAIA student-athletes to offer an in-depth look at the transition away from collegiate track and field. Mediation analysis was utilized to explore the interplay between commitment to values driven behavior, psychological wellbeing and the vocational construct Correspondence. Results are discussed from traditional and contemporary viewpoints, and limitations and suggestions for future research are provided.
Keywords: Acceptance; Mental Health; Sport Psychology; Track and Field; Transition